DISTANCE TUTORIALS WITH SKYPE - Sánchez, María Jesús; Diego, Carmen (Bordón. Revista de Pedagogía, 2015)
INTRODUCTION. The primary objective of this research is to check how to best encourage students to participate in tutorials. METHODOLOGY. The study used Skype, a tool with great potential for enhancing oral skills in foreign languages (Coburn, 2010; Eaton, 2010a, 2010b; Motlik, Nolletti and Vlamakis, 2012; Rimando, 2011; Tsukumato, Nuspliger and Senzaki, 2009; Yang and Chang, 2008). This study compared the participation of three groups of English Language I students randomly assigned to face-to-face (F-F) tutorials or distance tutorials with Skype (with or without additional credit). The study also compared the data with those belonging to a group of English Language II students (the English Language I group that had received additional credit). The only difference was that this group no longer received credit for its participation in tutorials via Skype. RESULTS. According to the working hypotheses, participation in the F-F tutorial was poor, with a greater participation in the group with tutorials via Skype that received extra credit. DISCUSSION. This research is very useful to diagnose the best type of tutorial to be developed in the future with English as a foreign language students (EFL), which is via Skype, as voluntary F-F tutorials do not seem to enhance learning. Nonetheless, the most significant result is students’ loyalty to the Skype system, even if they are no longer rewarded for their participation.